Implementasi PPh Pasal 4 Ayat 2 Dalam Sektor Ekonomi - Dini Anggraini; Maulida Rahma (CV. ITTC INDONESIA, 2024)
The majority of a country's budget comes from taxation. The main source of funding is taxes, which are used to promote national growth. Income taxes make the most money for the government. One of the purposes of final income tax is to supply services related to renting land and/or buildings, such as renting rooms. As stated in Income Tax Article 4 Paragraph (2), all company actors use accounting to document all transactions related to tax collection activities. Article 4 PPh is applied to the Indonesian economy in this article. Sources of income subject to this tax include providing construction services, renting land and buildings, and protecting property rights. This article highlights the ease of taxation, payment and tax reporting as an effort to cut administrative costs for both taxpayers and the Directorate General of Taxes (DJP). This research is a qualitative methodology; Specifically, it is a literature review that uses many citations from publicly available sources. The author offers a qualitative method by demonstrating how PPh paragraph 2 article 4 is applied in the economic sector. This research found that by emphasizing accountability and openness in financial activities, the implementation of this tax has helped expand the Indonesian economy.